Antibacterial Screenings of Chromolaena odorata L. and its potential against Staphyloccocus aureus, Bacillus subtilis, Staphyloccocus typhimurium, and Escherhicia coli in Sumbawa - Ainurrohmah Aulia; Khotibul Umam (Jurnal Biologi Tropis, 2022)
Kirinyuh plant extract is one of potential antibacterial sources. Metabolite extract of kirinyuh leaf extract, which contains tannins, flavonoids, saponins, and alkaloids, is known to have antibacterial activities. In order to demonstrate the effectiveness of kirinyuh leaf extract against the bacteria Staphyloccocus aureus (SA), Baciluss subtilis (BS), Staphylococus typhimurium (BT), and Escherhicia coli (EC), this study sought to identify the prosite of bioactive compounds as well as an antibacterial. The method used was leaf extraction and several doses level treatments of 0 (control), 1, 2, 4, 3, and 5 (concentrations of 20%, 40%, 60%, 80%, and 100%, respectively). This research findings showed that kirinyuh leaf extract has modest antibacterial activity against SA, BS, and ST, but that it has considerable inhibitory effect against EC. Together, this study demonstrated the potential of Kirinyuh as a antimicrobial to specific microbial since it has widely used in our society.